Digital media-induced tourism: The case of nature-based tourism (NBT) at East Java, Indonesia - Divinagracia, Louie A. (Animo Repository, 2012)
Digital media as an information resource and communication platform for tourists has significantly grown. Other than facilitating mobility and interactivity, digital media has likewise been instrumental in making convergence a reality. Convergence in media can be readily observed in tourism websites. The design of tourism websites are able to provide a virtual experience for tourists about a destination, and are able to influence the formation of a tourism destination image in their minds. Image management and image perceptions lie at the core of media induced tourism. The aim of this study is to determine the role of digital images on consumer choices within nature-based tourism (NBT) in East Java, Indonesia. It analyzed the mix of digital communication sources that are relevant and important in destination image formation, determined the motives of traveling to an NBT destination, and examined, among others, the changes in expected NBT destination attributes prior to and after exposure to a set of digital induced-images.